Video Eduksi ASI Ekslusif Sebagi Media Pemberikan Motivasi Ibu Hamil Trimester III - Fitria, Fitria; Fadhilah, Ummul; Mulyani, Sri; Lilis, Lilis (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service activity aims to increase the knowledge of pregnant women in the third trimester about the importance of exclusive breastfeeding, provide information about the benefits of breast milk, correct breastfeeding techniques, and the role of family support, and prepare mothers mentally and physically for the breastfeeding process after delivery. The activity method is carried out by playing educational videos compiled by the community service team, accompanied by interactive discussions and question and answer sessions. The videos contain information based on medical facts and are equipped with animations and illustrations to facilitate understanding. The activity was carried out by the PKM Team of the Undergraduate Midwifery Study Program, FKIK, Muhammadiyah University of Makassar in collaboration with the midwife team of PKU Muhammadiyah Unismuh Hospital Makassar, with a total of 10 participants of pregnant women in the third trimester. The results of the activity showed an increase in interest and enthusiasm from participants in providing exclusive breastfeeding. As many as 90% of participants stated that the educational video was very helpful in understanding the importance of breast milk, and 80% of participants stated their readiness to provide exclusive breastfeeding after giving birth. This activity went well thanks to the positive response from participants and support from health workers at the hospital.